Dampak Faktor Eksternal dan Faktor Internal terhadap Perkembangan Bank Umum Syariah di Indonesia - Luthfiah Nurazlina; Hasbi Assidiki Mauluddi (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
The goal of this study was to determine the impact to which external factors such as GDP growth, inflation and BI interest rate and internal factors such as CAR, FDR and NPF have had an influence on the development of Islamic Banks in Indonesia that represented by the growth of total assets Islamic banks in Indonesia from 2015-2019. This research used a quantitative approach and the data would be analyzed using multiple regression test through panel data regression with partial test and simultaneous test provided by Eviews 10. Considering the results of the simultaneous testing, the study suggests that all variables had an impact on the development of the Islamic Bank. As for the partial test, from the external factors only the BI rate which gives a significant negative impact on the development of Islamic banks and from internal factors there are NPF and FDR which give significant negative impact. It was concluded that GDP, Inflation, and CAR did not affect the development of Islamic Banks in Indonesia.